PENGARUH THERAPY BEKAM BASAH TERHADAP TEKANAN DARAH PASIEN HIPERTENSI - Mulyati, Leli (Politeknik Kesehatan Kemenkes Bengkulu, 2013)
This study aims to determined the effected of wet cupping therapy on blood pressure in hypertensive patients. The study used a quasi-experimental method with one group pre-test and post-test without a control group. The study subjects total 30 respondents consisting of patients with hypertension. All subjects are given wet cupping treatment twice with an interval of 2 weeks. Blood pressure measurements made ​​before and after wet cupping. The results of analysis used a t-dependent, decrease in average systolic blood pressure was 13 333 ± 12 042 wet cupping mmHg and diastolic 4667 ± 3294 mmHg. At week 2 a decrease in average systolic blood pressure mmHg while the 8667 ± 8308 6667 ± 5525 mmHg diastolic. Decrease in average systolic and diastolic blood pressure there were significant differences (p <0.05) in the first wet cupping and second wet cupping. This shows that wet cupping therapy affects blood pressure in hypertension patients.